Generation and characterization of BAC transgenic mouse lines expressing a fluorescent protein in trigeminal and dorsal root ganglion neurons - Piu Banerjee; Takuya Sato; Takuji Iwasato (PLoS ONE, 2025)
Genetic tools to identify and isolate specific cell types are required to study different model systems in an organism. Such tools to study sensory neurons in trigeminal and dorsal root ganglia are insufficient, making research progress in somatosensation difficult. Our study aimed to distinctly visualize and identify these peripheral sensory neurons in the mouse somatosensory system. We generated bacterial artificial chromosome transgenic mouse lines expressing the red fluorescent protein (RFP) in nuclei of Advillin (Avil)-positive neurons to help with the scarcity of bioresources. In these mice, RFP was specifically expressed in the trigeminal ganglion (TG) and dorsal root ganglion (DRG) in adulthood, consistent with previous reports. We also assessed RFP expression in the TG and DRG of these mice during embryonic and postnatal development. The TG RFP expression became evident around embryonic day 16.5 and continued across the postnatal period; in the DRG, it became apparent around postnatal day 0, continuing further. Lastly, almost all TG neurons (~90%) expressed RFP. These transgenic lines are valuable for studying the murine somatosensory system across developmental stages.